Impact of antirotational implants on cutout risk in cephalomedullary fixation of intertrochanteric fractures in elderly - Ömer Can Ünlü; İbrahim Altun; Muhammed Melez; Kürşat Tuğrul Okur; Firat Ozan (Medicine, 2026)
This study compared the impact of 2 antirotational implants on cutout risk and mid-term clinical outcomes in elderly patients with intertrochanteric femur fractures. Overall, 107 patients (mean age, 80.10 years) who underwent intramedullary nailing for intertrochanteric femoral fractures between April 2018 and December 2020 were included in this study. Patients were divided into 2 groups: those treated with Antirotator Proximal Femoral Nail (A-PFN; group A) and those treated with Interclaw Proximal Femoral Nail Antirotation (group I). This study evaluated lag screw positioning using the Bosworth–Cleveland scale, reduction quality based on Baumgartner’s criteria, tip-apex distance (TAD) values, cutoff values for TAD determined by receiver operating characteristic analysis, time from trauma to surgery, complications, and Harris Hip Score at the final follow-up. The mean follow-up durations were 18.4 ± 8.8 and 16.15 ± 4.72 months in groups A and I, respectively; operative times were 89.38 ± 30.45 and 71.15 ± 27.87 minutes, and time from trauma to surgery was 1.94 ± 1.52 and 1.56 ± 1.12 days, respectively. Nine patients required revision surgery because of implant failure: 2 nail breakages, 6 cutouts, and 1 periprosthetic fracture. No significant difference in complications was observed between the groups ( P = .812). Baumgartner’s criteria showed good results in 86.8% and 89.7% of groups A and I, respectively ( P = .765). The Cleveland scale indicated good outcomes in 79.4% and 69.2% of patients, respectively ( P = .237). Mean TAD was 23.6 ± 1.14 for group A and 25.7 ± 1.19 for group I ( P = .432), with a receiver operating characteristic analysis cutoff of 31.3. Harris Hip Score showed a stronger functional advantage in group I, with 85.5 points versus 77.5 points in group A ( P < .001). While both implants provided effective fixation, proper screw placement and anatomical reduction remained key factors in minimizing cutout risk, regardless of implant design.